DAMPAK WAKTU PEMANENAN YANG BERBEDA TERHADAP KUALITAS DAN KUANTITAS MICROGREENS BAYAM MERAH (Amaranthus tricolor L.) - Benedick Benedick; Theresa Dwi Kurnia (Journal of Innovation Research and Knowledge, 2025)
Microgreens are young plants that are harvested in the early growth phase and are known to have high nutritional content. This study aims to determine the effect of harvest time on the content of vitamin C, beta-carotene, and anthocyanin in red spinach microgreens (Amaranthus tricolor L.) grown using cocopeat media. The harvest treatment was carried out on days 14, 16, 18, 20, and 22. The results showed that the content of the three compounds increased until day 18, then decreased on the following days. The increase occurred along with the active growth phase of the plant, while the decrease was influenced by the aging process and degradation of bioactive compounds. Thus, day 18 is the optimal harvest time to obtain the highest content of vitamin C, beta-carotene, and anthocyanin in red spinach microgreens.